A study of policing mental health distress using linked administrative data in Scotland - McVie, Susan; Kurpiel , Allison (International Journal of Population Data Science, 2025)
Objectives This research aims to improve understanding of (1) the frequency and nature of police interactions related to mental health distress and (2) the characteristics of people who have contact with Police Scotland while experiencing mental health distress, thus helping to improve organisational responses to and services for people in distress. Methods Using linked administrative datasets from Police Scotland and Public Health Scotland, this research examines the prevalence of one-time and repeated police contacts related to mental health distress over a two-year period. We then descriptively compare the cohort of individuals who have been in contact with the police due to mental health distress to the general Scottish population in terms of their socio-demographic characteristics, health vulnerabilities, and healthcare use. Results Existing data indicates that police contact for mental health distress was highly prevalent in Scotland between 2022 and 2024. We expect our study to show that these types of incidents are concentrated among a subset of the population, such that a core group of individuals have multiple contacts. We also expect to find that individuals in contact with the police for reasons related to mental health distress differ from the general Scottish population in some important respects across the domains of socio-demographic traits, health vulnerabilities, and their use of the healthcare system. Conclusion This presentation will conclude that public health approaches to policing and cross-agency collaboration with the sector of public health are warranted, and that such efforts should be built around a solid evidence base to aid in the development of better informed, more effective policies.